Analisis Yuridis Keabsahan Perjanjian Jasa Parkir Tanpa Pemberian Bukti Transaksi Ditinjau dari Undang-Undang Perlindungan Konsumen - Dimas Aditya Rahman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This research aims to analyze the legal position of the relationship between managers and users of parking services according to the Civil Code, as well as to assess the validity of parking service agreements without proof of transaction in the perspective of Law Number 8 of 1999 concerning Consumer Protection. This research uses a normative juridical method with a legislative and conceptual approach. The results of the research show that based on Article 1320 of the Civil Code, a parking service agreement which is a custody agreement remains valid and binding even if it is not accompanied by written evidence, as long as it meets the requirements for a valid agreement. However, from the perspective of the Consumer Protection Law, the failure to provide transaction evidence constitutes a violation of the business operator's duty of good faith and the consumer's right to clear information. This creates legal uncertainty and weakens the consumer's position in seeking compensation, especially if accompanied by an exculpatory clause prohibited by law. Translated with DeepL.com (free version).